Impacts of the COVID-19 Response on the Domestic Violence Workforce - Wells, Sarah A. (Journal of interpersonal violence, 2024)
Many frontline and essential workers faced increased levels of stress, anxiety, depression, and even suicide ideation during the pandemic response. These and other factors led to burnout, shifts into non-patient or client-facing roles, or leaving an occupation altogether. Domestic violence advocates experienced increases in many types of stressors as they continued to provide essential services to victims and survivors during the pandemic. However, in most cases they did so without protections offered to essential workers, like priority access to personal protective equipment (PPE) or vaccines. Executive directors of U.S. State and Territorial Domestic Violence Coalitions were identified using the National Network to End Domestic Violence website and contacted via email to schedule key informant interviews. Interviews were conducted, recorded, and transcribed using Zoom. Themes were identified using both inductive and deductive coding. Twenty-five of 56 (45%) coalition executive directors completed an interview. Three main themes related to workforce were identified, including an accelerated rate of job turnover among both leadership and staff; a lack of essential worker status for domestic violence advocates; and unsustainable levels of stress, fear, and exhaustion. While familiar challenges drove these outcomes for this predominantly female, low-wage workforce, such as a lack of access to childcare, other factors, including the lack of access to PPE, training, and hazard pay for those working in person, highlighted inequities facing the domestic violence workforce. The factors identified as impacting the domestic violence workforce—turnover, low status, and high levels of stress, fear, and exhaustion—made the already challenging provision of advocacy and services more difficult. Domestic violence advocates are essential first responders and must be supported in ways that increase the resilience of empowerment-based services for victims and survivors.